Uterine Sarcomas: Are There MRI Signs Predictive of Histopathological Diagnosis? A 50-Patient Case Series with Pathological Correlation. (1st July 2021) - Hélage, Siegfried; Vandeventer, Stéphanie; Buy, Jean-Noël; Bordonné, Corinne; Just, Pierre-Alexandre; Jacob, Denis; Ghossain, Michel; Rousset, Pascal; Dion, Élisabeth
Abstract : Purpose . To make clear distinction between two radiological types of uterine sarcomas. Methods . 50 preoperative MRI were analyzed retrospectively, blinded to histopathology: 11 endometrial stromal sarcomas (ESS), 19 leiomyosarcomas (LMS), 18 carcinosarcomas/malignant mixed Mullerian tumors (MMMT), and 2 smooth muscle tumors of uncertain malignant potential (STUMP). Results . According to their locations, two radiological types of sarcomas were identified: type 1: intracavitary (ESS, MMMT) and type 2: intramyometrial (LMS, STUMP). In both types, all tumors displayed intermediate T2-weighted signal (p < 0.001 ) and high diffusion-weighted imaging (DWI) b1000 signal (p < 0.001 ). Dynamic contrast-enhanced (DCE) MRI showed intratumoral pathologic vessels (98%) and heterogeneity at venous phase (p < 0.001 ). In the type 1 subgroup, all tumors displayed local spread: invasion of junctional zone on T2-weighted imaging (T2WI), irregular margins on DWI, and disruption of arcuate arteries subendometrial ring on DCE-MRI. In the type 2 subgroup, all tumors displayed irregular margins on T2WI, DWI, and DCE-MRI. Tumor heterogeneity was due to necrosis (p < 0.001 ). Most commonly the tumor was single (61%). In both types, apparent diffusion coefficient (ADC) lesser than or equal to 0.86 × 10 −3 mm 2 /s (sensitivity = 73%, specificity = 92%) was suggestive of malignancy. Conclusion . It may be feasible to get close to histological type of a uterine sarcoma based on our topographic classification into two radiological subgroups, corresponding to two kinds of diagnostic difficulties. Advances in knowledge . MRI signs suggestive of histopathological malignancy are identifiable, considering the triad T2WI/DWI/DCE-MRI, easily for type 1 but less easily for type 2; the threshold value for ADC is 0.86 × 10 −3 mm 2 /s.